The Screening of Rubella Virus, Cytomegalovirus, Hepatitis B Virus, and Toxoplasma gondii Antibodies in Prepregnancy and Reproductive-Age Women in Tabriz, Iran - Edris Nabizadeh; Anahita Ghotaslou; Behnaz Salahi; Reza Ghotaslou (Hindawi Limited, 2022)
Objectives. The organisms of Toxoplasma gondii, Rubella virus, Cytomegalovirus, and Herpes simplex virus as an acronym of TORCH are major pathogens in prepregnancy and reproductive-age women. These microorganisms are considered a serious problem and cause 2-3% of all birth defects in the fetus. Our study was aimed at screening the seroprevalence of TORCH antibodies among prepregnancy and reproductive-age women in Tabriz, Iran. Design and Setting. This study was carried out in 2726 prepregnancy and reproductive-age women, who were referred to the laboratory for prenatal TORCH screening. To detect the presence of IgG, IgM antibodies and Hepatitis B surface antigen against these microorganisms were carried out using a chemiluminescence immunoassay analyzer (CLIA). Results. In the current study, the rates of anti-Toxoplasma gondii IgG, anti-Rubella virus IgG, and anti-Cytomegalovirus IgG were found in 722 cases (26.5%), 2579 cases (94.6%0), and 2718 cases (99.7%), respectively. Moreover, the rates of anti-Toxoplasma gondii IgM, anti-Rubella virus IgM, and anti-Cytomegalovirus IgM were discovered in 10 cases (0.4%), 13 cases (0.5%), and 16 cases (0.6%), respectively. The Hepatitis B surface antigen was found in 32 cases (1.2%). The dissemination of positive TORCH in various ages was different (P<0.05). Conclusions. In our study, the seroprevalence of acute TORCH infections was relatively low. Due to the probability of vertical transmission to the fetus during pregnancy and the unpleasant complication of these pathogens, it is essential to be screened for detection of specific IgG and IgM antibodies in reproductive ages.